PENERAPAN PENDIDIKAN SPIRITUAL PADA ANAK USIA DINI DALAM BUKU KOMIK 100 KEBIASAAN NABI - Subur Subur; Heru Kurniawan; Nur Hafidz (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2022)
The rise of education is currently faced with many cases of crime against children and adolescents, so that many become victims of violence, bullying, sexual abuse, and irregularities in the prevailing norms. Of course this is the duty of parents as first educators and teachers as educators in schools must be committed to overcoming and reducing current problems. The application of spiritual education is one of the efforts that needs to be instilled in early childhood. The application of spiritual education through children's reading books in the form of the 100 Habits of the Prophet Comic by Wawan Kungkang and Straightedge Dw. The purpose of this study was to describe and analyze the spiritual education of children in the comic book 100 Habits of the Prophet. This research method uses library research in reviewing books for research materials. The data source is from the comic book 100 Habits of the Prophet, the data collection technique uses documentation. then, the data analysis is carried out in three stages through; (1) data reduction, (2) data presentation, (3) verification and conclusion. The results of this study indicate the application of spiritual education to children in the comic book 100 Habits of the Prophet by Wawan Kungkang and Straightedge Dw. Through advice in educating children, habits in educating children, and prohibitions in educating children.